Ten-year evolution of world swimming trends for different performance clusters: a gaussian model - Veiga, S.; Grenouillat, A.; Rodríguez-Adalia, L.; Zarzosa-Alonso, F.; Pla, R. (International Journal of Sports Physiology and Performance, 2024)
Purpose: To analyze the evolution of the world ranking in swimming over the last 10 years, with particular attention to the effects of COVID-19 on the different levels of participating athletes.